Single nucleotide polymorphism analysis of the peroxisome proliferator-activated receptor gamma gene in type 2 diabetes mellitus patients at Ministry of Defense Hospital, RSPPN Soedirman Jakarta - Luluk Sakdiyyah; Apip Hadi; Yustinus Maladan; Syahrul Tuba (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
Type 2 diabetes mellitus is a metabolic disorder influenced by genetic and environmental factors. The Peroxisome Proliferator-Activated Receptor Gamma gene is known to play a role in T2DM pathogenesis, but its polymorphism profile in Indonesian patients remains poorly characterized. This study aimed to analyze single nucleotide polymorphisms in the PPAR-γ gene of T2DM patients at Rumah Sakit Pusat Pertahanan Negara (RSPPN) Soedirman Jakarta using adaptive sampling with nanopore sequencing. Eighteen DNA samples that passed quality control were analyzed using UGENE v52.1. A total of 26 SNPs were identified in 8 subjects, including C161T, which has a reported protective effect in T2DM. The clinical significance of the remaining SNPs remains unclear. This study provides initial insights into genetic variation in T2DM, which may contribute to personalized medical strategies for military personnel and support the development of a more resilient national defense health system by improving disease prevention and management in high-risk populations.